A new species of Craterium (Myxomycetes, Physaraceae) growing on living grass and new records of the genus from China - Zhang, Bo; Ma, Haixia; Li, Zhuang; Li, Yu; Li, Xiao (Phytotaxa, 2020)
A new species of Craterium (C. subpurpurea) collected in the Changbai Mountain National Nature Reserve, Jilin Province, northeastern China, is described. The fruiting bodies of C. subpurpurea are long cylindrical with distinct ridges, with large spinulose spores (8–10 μm diam.) as well as a persistent purplish pale peridium at the base of the sporotheca. A newly described species, C. aureonuleatum, has been documented in China for the first time, based on material collected from the Shennongjia National Nature Reserve, Hubei Province and the Gexigou National Nature Reserve, Sichuan Province. Craterium aureonuleatum is characterized by a yellowish pseudocolumella at the apex of the sporocarp and a persistent cup-like peridium when mature. Descriptions and scanning electron micrographs for these members of the genus Craterium are provided.